1996
DOI: 10.1046/j.1365-2567.1996.d01-704.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of cytotoxic T‐cell response by optimal‐length peptides does not require CD4+ T‐cell help

Abstract: SUMMARYIn several experimental models, synthetic peptides were shown to activate efficiently cytotoxic Tlymphocyte (CTL) responses and therefore represent an attractive strategy to develop new vaccines. However, the mechanisms by which they induce CTL responses are not yet fully understood. Several studies using 15-16-mer peptides previously demonstrated that CD4helper T cells are required to induce optimal CTL responses with synthetic peptides. However, recently, it was suggested that shorter 8-12-mer peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 22 publications
1
37
0
Order By: Relevance
“…CD4 þ T-helper cells play also a key role in the establishment of the CTL response. [47][48][49] MART1 mRNA lipopolyplexes also induced CD4 þ IFN-g-positive T cells. There are growing bodies of evidence showing that in humans one epitope of MART1 can be presented via MHC class II leading to a stimulation of CD4 þ T cells inducing a IFN-g secretion.…”
Section: Discussionmentioning
confidence: 90%
“…CD4 þ T-helper cells play also a key role in the establishment of the CTL response. [47][48][49] MART1 mRNA lipopolyplexes also induced CD4 þ IFN-g-positive T cells. There are growing bodies of evidence showing that in humans one epitope of MART1 can be presented via MHC class II leading to a stimulation of CD4 þ T cells inducing a IFN-g secretion.…”
Section: Discussionmentioning
confidence: 90%
“…CD4 ϩ Th cells play an important role on the induction of CTL (23,(31)(32)(33)(34). However, it has also been described that depletion of CD4 ϩ T cells may favor the induction of CTL responses (14,22,35), and enhance the therapeutic efficacy in tumor rejection (14,35) suggesting that CD4 ϩ T cells play a regulatory role.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies, including our own, have described the role of CD4 ϩ T cells in providing help for the induction of CTLs (23,(31)(32)(33)(34)36). However, CD4 ϩ T cells can coordinate other antitumor effector pathways independent of CTLs (37).…”
Section: Discussionmentioning
confidence: 99%
“…14,15 In addition to those artificial polyepitope vaccines, naturally linked and usually overlapping CTL and T h epitopes also performed well as vaccines in preclinical mouse models. 16,17 Furthermore, naturally occurring, linked CTL and T h epitopes with improved immunogenicity are present in humans, such as human papillomavirus (HPV), 18,19 NY-ESO-1 (a cancer testis antigen), 20 and HER-2/neu. 21,22 One of the major mechanisms for the enhanced vaccine potency of long peptides is most likely that, unlike 8-mer to 10-mer CTL epitopes, these are not able to bind directly to MHC class I molecules, so their presentation to CTL precursors must follow processing by DCs.…”
Section: Therapeutic Vaccines Combined With Chemotherapymentioning
confidence: 99%
“…The necessity of CD4-positive T-cell help to generate and sustain the MHC class I-restricted, CD8-positive T-cell responses has led to the use of MHC class II-restricted epitopes derived from the same protein 16,35 and also to universal, nonspecific MHC class II-restricted epitopes, such as pan-DR T h epitope (PADRE), in clinical vaccination trials that included patients with melanoma who were immunized with melanoma antigen 3 (MAGE-3) CTL peptides and patients with cervical carcinoma who were vaccinated with HPV16 E7 CTL peptides. 36,37 Although those studies demonstrated the capacity of PADRE to induce potent responses to PADRE itself, this did not increase CTL activity.…”
Section: Clinical Trials Using Polyepitope Long-peptide Vaccinesmentioning
confidence: 99%